Analysis of Tubespins as a suitable scale‐down model of bioreactors for high cell density CHO cell culture. (28th January 2017) - Gomez, Natalia; Ambhaikar, Malhar; Zhang, Li; Huang, Chung‐Jr; Barkhordarian, Hedieh; Lull, Jonathan; Gutierrez, Chris
Abstract : High cell density (HCD) culture increases recombinant protein productivity via higher biomass. Compared to traditional fed‐batch cultures, HCD is achieved by increased nutrient availability and removal of undesired metabolic components via regular medium replenishment. HCD process development is usually performed in instrumented lab‐scale bioreactors (BR) that require time and labor for setup and operation. To potentially minimize resources and cost during HCD experiments, we evaluated a 2‐week 50‐mL Tubespin (TS) simulated HCD process where daily medium exchanges mimic the medium replacement rate in BR. To best assess performance differences, we cultured 13 different CHO cell lines in simulated HCD as satellites from simultaneous BR, and compared growth, metabolism, productivity and product quality. Overall, viability, cell‐specific productivity and metabolism in TS were comparable to BR, but TS cell growth and final titer were lower by 25 and 15% in average, respectively. Peak viable cell densities were lower in TS than BR as a potential consequence of lower pH, different medium exchange strategy and dissolved oxygen limitations. Product quality attributes highly dependent on intrinsic molecule or cell line characteristics (e.g., galactosylation, afucosylation, aggregation) were comparable in both scales. However, product quality attributes that can change extracellularly as a function of incubation time (e.g., deamidation, C‐terminal lysine, fragmentation) were in general lower in TS because of shorter residence time than HCD BR. Our characterization results and two case studies show that TS‐simulated HCD cultures can be effectively used as a simple scale‐down model for relative comparisons among cell lines for growth or productivity (e.g., clone screening), and for investigating effects on protein galactosylation. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:490–499, 2017